Influence of implant number on the retention and support of mandibular overdentures - Al-Bdrany, Ahmed A.; Sadoon, Mohammed M. (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: There are two distinct categories of attachments—magnetic attachments and positioner attachments—currently in use for dental implants. Many implants required for implant-retained overdentures need support from implant-retained overdentures. Purpose: The aim of this study is to evaluate the effect of different implant numbers and attachment types on the retention and support of implant-retained overdentures. Methods: This experimental work involved the utilization of a model that replicated a mandibular edentulous arch, a total of five models. Within this model, seven dental implant analogues were implanted to mimic the tooth positioning observed in the natural dentition. Thirty-five titanium dental implant analogues (Dentium, South Korea) were employed in this study. A total of ten overdenture housings were fabricated using 3D printer acrylic resin, with each housing including a specific type of attachment (magnetic and positioner attachment). These attachments were equipped with three loops that were affixed to the occlusal surface of the housing. Subsequently, three chains were connected between the loops and a force gauge testing equipment. Results: The positioner was found to be more retentive and supportive than the magnetic one in the three directions of the dislodgement test as well as under unilateral and bilateral load, according to an independent t-test comparing magnetic and positioner attachment (p<0.05). Conclusion: Depending on the method of attachment that is used, variations in implant number have varying effects on the retention and support of an implant-held overdenture.